Experience of implementation of D-PBL methodology with virtual patients and medical errors in surgery at Zaporizhzhia state mdical university - Avramenko, М. О.; Furyk, O. О.; Авраменко, Микола Олександрович; Фурик, Олена Олександрівна (My University, 2018)
The article presents data on implementation of D-Problem-Based Learning method using virtual patients with medical errors in surgery as part of the TAME: Training Medical Against Error project. Training students in a safe environment using the D-PBL method with virtual patients and medical errors in surgery contributed to athe improving of level of knowledge in the discipline (p <0.01) and results of the sub-test “Surgical profile” of the State Licensing Examination KROK- 2 (p <0,05), in comparison with the results of control group students. A comparative analysis by gender showed that students of the 2nd group (female) had higher (p <0.01) results compared to the 1st group on the state licensing examination “KROK-2” and sub-test “Surgical profile” of the State Licensing Examination KROK-2 (p <0, 05).In the future medical career it will become the basis for avoiding medical errors, limiting further harm and improving overall healthcare safety. У статті наведені дані щодо впровадженняя методу D-проблемно-орієнтованого навчання з використанням віртуальних пацієнтів з медичними помилками в хірургії в рамках проекту «ТАМЕ: навчання на медичних помилках». Навчання студентів у безпечних умовах за методикою D-PBL з використанням віртуальних пацієнтів з медичними помилками в хірургії сприяло підвищенню рівня знань з дисципліни (р<0,01) й субтесту «Хірургічний профіль» державного ліцензійного іспиту «КРОК- 2» (р<0,05), проти результатів студентів контрольної групи. При порівняльному аналізі за гендерною ознакою виявлено, що студенти ІІ групи (жіночої статі) мали вищі (р<0,01) результати від І групи з державного ліцензійного іспиту «КРОК-2» та субтесту «Хірургічний профіль» (р<0,05). У майбутній професійній діяльності це стане основою запобігання медичних помилок, зменшення шкоди та підвищення загального рівня медико-санітарної допомоги.
Keywords: Problem-Based Learning; virtual patients; medical errors; проблемно-орієнтоване навчання; медичні помилки